Tensegrity : Structural Systems for the Future. - Motro, René (Elsevier, 2003)
The word tensegrity results from the contraction of?tensional? and?integrity?, a word created by Richard Buckminster Fuller. He went on to describe tensegrity structures as?islands of compression in an ocean of tension?, and René Motro has developed a comprehensive definition which is?systems in a stable self equilibriated system comprising a discontinuous set of compressed components inside a continuum of tensioned components?. This publication represents the life work of a leading exponent of a revolutionary and exciting method of structural design.